Examining the effectiveness of an embedded language education programme for international health science students in an Irish university - Kelly, Helen Margaret (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2023)
This study examines the effectiveness of an embedded language programme for international English as an Additional Language (EAL), health science students studying on a medicine or physiotherapy degree at an Irish university. The research examines the impact of this educational programme on learners? language and communicative competence development in terms of both language gains in domain specific contexts and the fostering of language learner autonomy. This study also evaluates the extent to which learners benefit from intercultural communicative competence and awareness as it relates to their needs as both international learners and healthcare students training in a clinical environment. The study includes an extensive literature review across the fields of language learning theory and intercultural communicative competence and awareness studies, relating to both medical education and international student education contexts. This combination and inter-relationship of factors are considered in examining what a supportive learning environment for this learner group might look like. The evaluation considers approaches to language programmes for learners in higher education from the lens of content-integrated, context-relevant or embedded language learning and curricula design. This research investigates the possible benefits of a combination of factors (linguistic, intercultural, personal, sociocultural and medical domain specific) to the acquisition of language and learning skills for this learner group through the analysis of the data. The author has enquired into the factors that may positively advance domain specific or targeted language acquisition and cultural learning in a supportive, inclusive, holistic approach to educating international students studying through English as an additional language. The methodology for this research is a mixed methods study, examining qualitative and quantitative findings in a sequential, systematic, and blended approach. This research includes analysis of questionnaires and semi-structured interviews with students and staff, as well as supplemental learner classroom feedback consideration. The qualitative reflective thematic analysis (RTA) takes a deductive approach to thematic analysis using Braun and Clarke?s 6-step RTA approach. The findings clearly show that the programme under evaluation had a significant positive impact on the participants in all areas of the investigation including language gains and confidence, learner autonomy advances, increased intercultural competence and communicative competence in medical and healthcare domains. Despite challenges identified around the complexity of delivery of a programme embedded in the learning in this way and the fact that the time allowed for the programme was not sufficient for a minority of learners, the findings support the conclusion that the benefits of this programme significantly outweigh the challenges. Overall, we can say that the programme was viewed as supporting the needs of these international students in their learning environment.
APPROVED
Keywords: language learner autonomy; English language programmes in higher education; language learning at university; Intercultural communicative competence; International medical students; context-embedded language programme; EAP; intercultural healthcare education